A review of past and present summer primary production processes in the Ross Sea in relation to changing ecosystems - Mangoni, Olga; Saggiomo, Vincenzo; Bolinesi, Francesco; Escalera, Laura; Saggiomo, Maria (2018)
We analyse primary production processes during austral summer 1996 and 2001 in different environmental conditions such as ice-free waters and extensive ice-covered areas. Spatio-temporal distribution of phytoplankton biomass and functional groups along with photosynthetic parameters are presented. Production vs irradiance (PvsE) experiments were performed using 14C incubations at several stations and three or four different depths to define the eco-physiology of phytoplankton communities. The results of the oceanographic campaign conducted in ice-free waters of the Ross Sea (summer 1996) emphasize that these ecosystems are characterized by high nutrient low chlorophyll (HNLC) conditions due to limiting factors (eg. Fe). Conversely, the results of the oceanographic cruise in extensively packice-covered areas (summer 2001) indicate that the average phytoplankton biomass (estimated from Chla) was about three times the values recorded in ice-free conditions, but the primary production was relatively lower. In fact, in situ primary production and PvsE experiments over few days show that high primary production values occurred in most of the area, but only within the first five meters of the water column and the melting pack ice. Notwithstanding some high values of phytoplankton biomass during the 2001 campaign, water column stability, similar irradiance levels along the water column, photosynthetic capacity was suppressed in deeper layers, indicating a low carrying capacity of the pelagic ecosystem due to iron limitation, as shown by low values of the photo-chemical efficiency of photosystem II (PSII), variable fluorescence and maximal fluorescence ratio (Fv/Fm). In contrast with a very high variability in phytoplankton biomass at several temporal and spatial scales, photosynthetic parameters (PB max , α, Ek) varied within narrow ranges. Relevant changes in phytoplankton abundance and species composition are reported in this study although the environmental factors that drive these changes in primary production ...